The training of the math teacher: looking for pathways to overcome the difficulties at the beginning of the career (Research, Society and Development, 2018)
The present article aims to discuss the formation of the math teacher at the begin of his career, highlighting the challenges and difficulties faced by the school reality. The discussion was developed through a qualitative approach, and the content collected through half structured interviews with six mathematics teachers from public and private schools with up to three years of teaching was analyzed. In the course of these studies and from the dialogue with texts by researchers like Tardif and Raymond, Huberman, Cavaco and Guarnieri, we note the importance of researching on the challenges and difficulties experienced by the teacher of mathematics at this early stage. The results obtained allow us to affirm the importance of reflection on how each one becomes a teacher and the formation of the future teacher of mathematics as a space of articulation between theory and practice. We consider that it is necessary to insert policies to support the beginning teacher, because it is at this stage that the challenges begin to appear, shaping the identity of the teacher and giving new characteristics to the professional.